Dystocia in a gilt due to ascitic fetus- a case report - HONPARKHE, M; KUMAR, AJEET; PRABHAKAR, S; SATHYA, A (The Indian Journal of Animal Reproduction, 2023)
The present case report puts on record a case of dystocia due to ascitic piglet, accompanied by mummified and stillborn fetuses and their successful delivery with obstetrical manoeuver.